The Effects of Artificial Turf on the Performance of Soccer Players and Evaluating the Risk Factors Compared to Natural Grass - Yasamin Alipour Ataabadi; Heidar Sadeghi; Mohammad Hosein Alizadeh (Journal of Neurological Research And Therapy, 2017)
The global popularity of soccer has led to widespread tendency towards this sport. Because of the convenience of using artificial surfaces, the rapid growth of using these surfaces led to concerns about the declining performance of the players. The aim of this comprehensive review is to study the difference between the performance of players on different playing surfaces and the risk factors for use of artificial turf compared to natural grass. A literature search of valid scientific databases such as Science Direct, PubMed and Jstor by searching keywords was performed. In total, more than 6,000 articles were retrieved. After the preliminary selection process, the final analysis was performed on a total of 76 articles. Results: Mechanical properties of artificial grass have a significant effect on the average time of sprinting, the best time of sprinting and maximum speed. The numbers of sliding tackles on artificial turf were lower compared to natural grass. Artificial turfs exposed hardness, elasticity and high friction. The characteristics of artificial grass have changed over time and increased the probability of injuries. There was no significant difference between the overall risks of acute injuries in soccer players performing on artificial turf compared to natural grass. The amateur, young and female soccer players had rated lower injuries on artificial grass. But the rate of injuries in elite soccer players were higher on artificial grass and hence they are not found of playing on such playing surfaces.
Keywords: soccer